2011
DOI: 10.1063/1.3620403
|View full text |Cite
|
Sign up to set email alerts
|

Relations between light emission and electron density and temperature fluctuations in a helium plasma

Abstract: The relations between three atomic lines, He I 667.8 nm (3 1 D ! 2 1 P), 706.5 nm (3 3 S ! 2 3 P), and 728.1 nm (3 1 S ! 2 1 P), and the underlying fluctuations in a helium plasma are investigated for the quantitative interpretation of optical observations in plasma fluctuation measurements. Frequency dependent fluctuation amplitude ratios and phase delays between the line emission fluctuation and the electron density and temperature fluctuations are calculated based on a quasi-static collisionalradiative mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
(80 reference statements)
1
10
0
Order By: Relevance
“…Ma et al looked at the response of the helium system over a wide range of frequencies and found that the simple CR model is adequate at MHz and slower frequencies. 136 More complex behavior was found at higher frequencies.…”
Section: Gpi Line Emission Processesmentioning
confidence: 92%
“…Ma et al looked at the response of the helium system over a wide range of frequencies and found that the simple CR model is adequate at MHz and slower frequencies. 136 More complex behavior was found at higher frequencies.…”
Section: Gpi Line Emission Processesmentioning
confidence: 92%
“…The energy levels, excepting the ground state, are assumed to satisfy the quasi-static approximation. 26 The recombining plasma component is neglected, since the ionizing plasma component is the dominant part for n e < 10 14 cm −3 and T e > 5 eV. 13 The ionizing plasma condition does not require the neutral density to be measured and this simplifies the diagnostic.…”
Section: B Helium Line Intensity Ratio Technique For N E and T E Meamentioning
confidence: 99%
“…It is planned to use the inferred plasma n e and T e information for characterizing the plasma temperature and density fluctuations. 26 In Sec. II, the tomography approach for reconstructing spectral line radiances and radiance ratios from line-of-sight measurements and the helium line intensity ratio technique based on a CR model are described.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the instant net power for channel heating is C l P e − P l and the channel accumulated heating energy will be W h = ∫( C l P e − P l ) dt . Physically, the light radiation power depends on the volume (or mass: Δ m ) fraction of air excited and the level of excitation (temperature: T ) during the return stroke, i.e., P l ~ T Δ m [ Ma et al ., ]. The channel rising temperature in turn depends on the accumulated heating energy and the heated mass, i.e., W h ~ ( T − T 0 ) Δ m , where T 0 is the initial gas temperature.…”
Section: Modeling Of Light and Electromagnetic Emissions From Return mentioning
confidence: 99%